PENDAMPINGAN ANAK DALAM MEMPERTAHANKAN BUDAYA LUHUR MELALUI PERWUJUDAN PROFIL PANCASILA - Ahmad Aly Syukron Aziz Al Mubarok; Nurul Hidayati; Ahmad Wisnu Saputra; Mira Soraya; Siti Aminatur Rizkiyah (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2023)
The definition of a Pancasila profile is the character and competence, or abilities that must be possessed by the Indonesian students of the 21st century. Character and competence are two different but interdependent things. Both are very important for every Indonesian student. Children who do not understand their own culture will feel confused because they cannot distinguish which culture is good and suitable for them when they encounter the influence of different foreign cultures caused by the development of information technology. The way to implement this PKM is through a participatory, question-and-answer approach as well as a reward and punishment method, starting with an introduction to the Pancasila Student Profile, developing Pancasila Student Profile Dimensions, and practicing Pancasila Profile Dimensions No. 2, i.e. Global Diversity through Musical Culture. The last activity produced is that SDN Ngastemi 1 children can foster enthusiasm, learn about noble culture, a sense of tolerance (mutual respect) and religious moderation. This activity can be carried out from Thursday, February 9, 2023 to Wednesday, March 8, 2023 for children of the third grade of primary school, with a total of 32 children. This activity received an enthusiastic response from the students of SDN Ngastemi 1 class 3. Apart from the excited children, the teachers also felt that this activity was important in raising awareness of their students.